2021 IEEE International Conference on Communications Workshops (ICC Workshops) 2021
DOI: 10.1109/iccworkshops50388.2021.9473681
|View full text |Cite
|
Sign up to set email alerts
|

Channel Modeling and Analysis of Reconfigurable Intelligent Surfaces Assisted Vehicular Networks

Abstract: The new concept named reconfigurable intelligent surfaces (RIS) is becoming an appealing enabler due to its uniqueness with having low hardware complexity and low power consumption advantages simultaneously. In this paper, an RISaided vehicular Adhoc network (VANET) is considered, where the beacon vehicle is enabled with a passive RIS, the communication links between the beacon vehicle and client vehicle caused due to the multipath fading effects, are modeled with Fox's H-function distribution. This paper firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…RIS, being an appealing approach, has become a hot topic for researchers from both wireless communication and signal processing communities [13]. The machine learning-enabled RIS-assisted wireless communication systems have been under exploration in terms of channel modelling [4], [14], channel estimation, EE [15], etc. More specifically, the authors in [4] and [14] applied the unsupervised machine learning tool, namely, the expectation-maximization (EM) algorithm to model the RIS-assisted wireless communication links.…”
Section: B Ris Related Researchesmentioning
confidence: 99%
See 2 more Smart Citations
“…RIS, being an appealing approach, has become a hot topic for researchers from both wireless communication and signal processing communities [13]. The machine learning-enabled RIS-assisted wireless communication systems have been under exploration in terms of channel modelling [4], [14], channel estimation, EE [15], etc. More specifically, the authors in [4] and [14] applied the unsupervised machine learning tool, namely, the expectation-maximization (EM) algorithm to model the RIS-assisted wireless communication links.…”
Section: B Ris Related Researchesmentioning
confidence: 99%
“…The machine learning-enabled RIS-assisted wireless communication systems have been under exploration in terms of channel modelling [4], [14], channel estimation, EE [15], etc. More specifically, the authors in [4] and [14] applied the unsupervised machine learning tool, namely, the expectation-maximization (EM) algorithm to model the RIS-assisted wireless communication links. It is also demonstrated that the machine learning methods are able to provide better performance than central limit theorem-based approaches [4] [14].…”
Section: B Ris Related Researchesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors [17] developed an iterative algorithm to optimize the RIS phase shifts for the data rate maximization of a RISassisted mmWave vehicular communication network. In [18], the authors studied the RIS-enabled vehicle-to-vehicle (V2V) communications using the Fox's H-function distribution. In [19], the placement of multiple RIS is optimized for vehicleto-everything (V2X) communications.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [9] applied series expansion and central limit theorem (CLT) to approximate the outage probability performance of the RIS-assisted vehicular communication assuming Rayleigh and Rician fading channels. In [11], the authors provided an approximate analysis on the outage probability and effective rate for RIS-assisted V2V communications over Fox's-H function by approximating the distribution of the signal-to-noise ratio (SNR) of the resultant channel as a mixture of Gaussian distributions. The authors in [12] evaluated the performance of RIS-enabled vehicular system considering joint impact of Fisher-Snedecor (F) fading channel and the vehicle mobility modeled as a random way point.…”
Section: Introductionmentioning
confidence: 99%